Association between sarcopenia and suicidal ideation in a nationwide population-based study - Eyun Song; Soo Yeon Jang; Min Jeong Park; Ahreum Jang; Kyeong Jin Kim; Ji Hee Yu; Nam Hoon Kim; Hye Jin Yoo; Ji A Seo; Sin Gon Kim; Nan Hee Kim; Sei Hyun Baik; et al. (Scientific Reports)
Abstract Sarcopenia may be associated with suicide through various mechanisms, including depression, physical disability, chronic diseases, and myokines. However, research on this topic has been limited. We analyzed individuals who participated in the Korea National Health and Nutrition Examination Survey from 2008 to 2011 and had available dual-energy X-ray absorptiometry data and information on suicidal ideation. Of the 17,615 individuals, 2,902 (16.5%) were categorized into the suicidal ideation group. Low muscle mass was more prevalent in the suicidal ideation group than in the non-suicidal ideation group (10.8% vs. 7.8%, respectively; p < 0.001). The results of a multiple logistic regression revealed a significantly higher odds ratio (OR) for suicidal ideation in participants with low muscle mass than in those without (OR, 1.25; p = 0.029), after adjusting for various confounding factors. This association was more pronounced in females than in males, and in those aged 50–79 years than in those aged < 50 or ≥ 80 years. Individuals with low muscle mass revealed a substantial association with an increased odd of suicidal ideation in the general Korean population. These results suggest that screening and interventions for sarcopenia may help prevent suicide, particularly among middle-aged females.